STRATEGI PENGELOLAAN MEDIA SOSIAL DALAM MEMBANGUN BRANDING DAN PORTOFOLIO VISUAL PADA MEDIA SOSIAL IMAGENIC - Oktaviany, Shafira; Priatna, Wahyu Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social media has become an important platform for companies to build branding and showcase their visual portfolios. This study aims to analyze the social media management strategy implemented by Imagenic in building branding and visual portfolios, describe the content planning, production, and distribution process, and examine its contribution to brand awareness and brand image based on Keller’s Customer Based Brand Equity (CBBE) model. The study was conducted during an internship at PT Kisah Tanpa Kata (Imagenic) from January to May 2026 using active participation, observation, interviews, and literature study methods. The findings show that Instagram serves as the primary platform for displaying wedding photography and videography portfolios, while TikTok, Pinterest, YouTube, Threads, and X support content distribution and audience engagement. Content management is carried out through evaluation, content curation, editing, revision, approval, and publication stages. A behind-the-scenes content uploaded on the TikTok account Life at Imagenic reached more than 1.3 million views, indicating strong audience interest in the creative process behind wedding documentation. The results demonstrate that consistent visual identity and structured social media management contribute to strengthening brand awareness, building a positive brand image, and maintaining relationships with audiences.